EVALUASI KELAYAKAN DAN PENINGKATAN KINERJA JALAN LINGKAR KUDUS - Asep Setyobudiato; Singgih Prasetyo; Bagus Hario Setiadji; Moga Narayudha (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Kudus Ring Road is a primary arterial road that connects traffic from the provincial capital of East Java’s Surabaya to the provincial capital of Central Java’s Semarang. This ring road was establised with the purpose to redirecting traffic without having to pass through the urban area, so it can reduced the traffic jam. First construction was started at 1997 and has several repairs or improvements. At an early age getting older, this ring road needs an evaluation for many fators such as traffic performance, road geometry, road pavement, drainage channel, and complement facility such as light lamp, road marker, and traffic’s signs. The results of the evaluation are expected to improve the quality of this ring road in serving the traffic movements.